2012
DOI: 10.4137/cmc.s8578
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Catheter Ablation in Children with Supraventricular Tachycardias: Intermediate Term Follow up Results

Abstract: The Purpose of the StudyRadiofrequency (RF) catheter ablation represents an important advance in the management of children with cardiac arrhythmias and has rapidly become the standard and effective line of therapy for supraventricular tachycardias (SVTs) in pediatrics. The purpose of this study was to evaluate the intermediate term follow up results of radiofrequency catheter ablation in treatment of SVT in pediatric age group.MethodsA total of 60 pediatric patients (mean age = 12.4 ± 5.3 years, ranged from 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 38 publications
0
11
1
6
Order By: Relevance
“…However, Vassilikos et al showed that non-cardiologists (general practitioners and internists) who are involved in the acute and long-term management of SVT rely more on antiarrhythmic drugs and tend to underestimate the role of ablation therapy for the long-term management of SVT (31). RF ablation therapy is increasingly used in pediatric patients with SVTs, however, antiarrhythmic therapy is still the first choice (usually guided on the results of transesophageal atrial pacing technique), in which propafenone is one of the first choices and has good efficacy in termination of tachycardias (32,33). All this points to the importance of antiarrhythmics for the treatment of supraventricular tachycardias, and therefore to the importance of propafenone, which has proven to be efficient in our study as well as several previous studies, although they included a small number of patients (23,27,28).…”
Section: Discussionmentioning
confidence: 99%
“…However, Vassilikos et al showed that non-cardiologists (general practitioners and internists) who are involved in the acute and long-term management of SVT rely more on antiarrhythmic drugs and tend to underestimate the role of ablation therapy for the long-term management of SVT (31). RF ablation therapy is increasingly used in pediatric patients with SVTs, however, antiarrhythmic therapy is still the first choice (usually guided on the results of transesophageal atrial pacing technique), in which propafenone is one of the first choices and has good efficacy in termination of tachycardias (32,33). All this points to the importance of antiarrhythmics for the treatment of supraventricular tachycardias, and therefore to the importance of propafenone, which has proven to be efficient in our study as well as several previous studies, although they included a small number of patients (23,27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Radiofrequency ablation (RFA) using the traditional radiofrequency energy to heat and destruct the site of origin of the SVT mechanism has been more widely applied in children since the 1990s [3]. It is now considered as the fi rst line of management for many children with SVT and offering the prospect of cure of the arrhythmia and avoidance of drugassociated side effects.…”
Section: Long Term (Chronic) Management Of Svt: the Decisionmentioning
confidence: 99%
“…Variable mechanisms of SVT exist; we concentrated on the three commonest forms occurring in children which are: atrioventricular re-entry tachyarrhythmia (AVRT), atrioventricular nodal re-entry tachyarrhythmia (AVNRT), and atrial tachyarrhythmia (AT) [3].…”
Section: Introductionmentioning
confidence: 99%
“…The main aetiology for cardiac arrhythmias in adults is myocardial damage due to coronary disease. In children, arrhythmia is rather inherited and closely associated with changes in the development of the cardiac conduction system [1], and supraventricular tachycardia (SVT) is responsible for 95% of cases [2]. Despite this fact, data about the heart rhythm disturbances in children are often extrapolated from the adult population.…”
Section: Introductionmentioning
confidence: 99%